EFEKTIVITAS MODEL PEMBELAJARAN TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DITINJAU DARI PRESTASI BELAJAR DAN SELF-EFFICACY MATEMATIKA SISWA SMP - Azwar Anwar; Rusgianto Heri Santosa (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
This study aims: (1) to describe the effectiveness of Team Assisted Individualization (TAI) type of cooperative learning model and scientific approach in terms of learning achievement and self efficacy, (2) comparing the effectiveness of Team Assisted Individualization (TAI) type of cooperative learning model and scientific approach in terms of learning achievement and self efficacy. The type of research used is quasi experimental research. The population in this study were class VII students of SMP Negeri 2 Depok. Data were analyzed descriptively, hypothesis testing using one-sample t-test, MANOVA test with T2 Hotteling formula. The results of the study are as follows. (1) The implementation of effective Team Assisted Individualization (TAI) type of cooperative learning model, while the scientific approach is not effective in terms of learning achievement and self efficacy. (2) The application of the Team Assisted Individualization (TAI) type of cooperative learning model is more effective than the application of the scientific approach.